A National Survey of Medical School Curricula on Criminal Justice and Health. (January 2019) - Simon, Lisa; Tobey, Matthew
The number of U.S. medical schools that provide clinical training in correctional facilities or classroom-based training in criminal justice–related issues is unknown. This study consisted of an online survey of deans of education at U.S. schools granting an MD degree to assess teaching regarding criminal justice and health, and clinical training in correctional settings. We compared perceptions of such training and perceptions of graduate preparedness between programs with and without correctional health curricula. Institutions that offered instruction in correctional health were significantly more likely to agree that their graduates believe incarceration to be a social determinant of health and that their graduates are prepared to care for incarcerated patients. A substantial number of U.S. medical schools offer teaching that links health and criminal justice, though the extent of curricula varies significantly.